Maintenance of Positional Identity of Neural Progenitors in the Embryonic and Postnatal Telencephalon - Delgado, Ryan N.; Lim, Daniel A. (Frontiers in Molecular Neuroscience, 2017)
Throughout embryonic development and even into adulthood, distinct populations of neural progenitor cells (NPCs) collectively generate the many different types of neurons that underlie the complex structure and function of the adult mammalian brain. Shortly after neural induction, NPCs in the early mouse embryo become organized into regional domains that each produce different subsets of neurons. The positional identity of NPCs relates to the regional expression of key fate-determining transcription factors that emerges early in embryogenesis. As development progresses, the brain undergoes vast changes in both size and shape, yet important aspects of NPC positional identity persist even into the postnatal brain. How can NPC positional identity, which is established so early in development, endure the many dynamic, large-scale and complex changes that occur during brain development? In this perspective, we discuss the segmental nature of embryonic telencephalon NPC zones and key aspects of these regional differences that persist in the postnatal NPCs of the postnatal ventricular-subventricular zone (V-SVZ). Using the V-SVZ as a framework, we explore several potential molecular mechanisms that might underlie the long-term maintenance of NPC positional identity.